What is the impact of muscle hypertrophy on strength and sport performance? - Hornsby, W. G.; Gentles, J. A.; Haff, G. G.; Stone, M. H.; Buckner, S. L.; Dankel, S. J.; Bell, Z. W.; Abe, T.; Loenneke, J. P. (Strength and Conditioning Journal, 2018)
For decades, most scientists and practitioners have agreed that muscle hypertrophy also induces strength gains. However, a recent publication "the problem of muscle hypertrophy: revisited," Buckner, SL; Dankel, SJ, Mattocks, KT, Jessee, MB, Mouser, JG, Counts, BR, et al. The problem of muscle hypertrophy: revisited. Muscle nerve 54: 1012-1014, 2016, questioned the mechanistic role that exercise-induced increases in muscle size have on the exercise-induced increases in strength (or force production), as well as the influence that exercise-induced increases in strength have on sports performance. Such suggestions undermine the importance of certain aspects of strength and conditioning for sport. Specifically, if not acting as a mechanism for strength adaptation, it is unclear if there is a sports-related benefit to skeletal muscle hypertrophy. In addition, the authors argued that if strength has little impact on sports performance, strength and conditioning programs may be doing little more than delaying recovery from practicing the actual sport. This contention also indicates that hypertrophy should be avoided in nearly all scenarios because increased muscle size would be additional mass that must be overcome. The purpose of this special discussion is to allow for an in-depth scientific discussion of the experimental evidence for and against the position of buckner et al. That exercise-induced increases in muscle size have little relevance on the exercise-induced increases in strength, and thus, sport performance.